Relative Expression of a Dominant Mutated ABCC8 Allele Determines the Clinical Manifestation of Congenital Hyperinsulinism - Shemer, Ruth (American Diabetes Association, 2012)
Congenital hyperinsulinism (CHI) is most commonly caused by mutations in the β-cell ATP-sensitive K(+) (K(ATP)) channel genes. Severe CHI was diagnosed in a 1-day-old girl; the mother’s cousin and sister had a similar phenotype. ABCC8 gene sequencing (leukocyte DNA) revealed a heterozygous, exon 37, six–base pair in-frame insertion mutation in the affected patient and aunt but also in her unaffected mother and grandfather. In expression studies using transfected COSm6 cells, mutant sulfonylurea receptor 1 (SUR1) protein was expressed on the cell surface but failed to respond to MgADP even in the heterozygous state. mRNA expression in lymphocytes determined by sequencing cDNA clones and quantifying 6FAM-labeled PCR products found that although the healthy mother predominantly expressed the normal transcript, her affected daughter, carrying the same mutant allele, primarily transcribed the mutant. The methylation pattern of the imprinting control region of chromosome 11p15.5 and ABCC8 promoter was similar for all family members. In conclusion, differences in transcript expression may determine the clinical phenotype of CHI in this maternally inherited dominant mutation. The use of peripheral lymphocytes as a peripheral window to the β-cell transcription profile can serve in resolving β-cell phenotypes. The severe, dominant-negative nature of the 1508insAS mutation suggests that it affects the functional stoichiometry of SUR1-regulated gating of K(ATP) channels.